EXPANDED DIMENSIONS OF THE PURPOSES AND USES OF PERFORMANCE APPRAISAL - Muhammad Zahid Iqbal (Asian Academy of Management Journal, 2012)
This paper attempts to develop an understanding of performance appraisal (PA) and to identify inconsistencies in its purposes and uses through an analysis of previous studies. The paper explores the purposes and uses of PA in the literature and devises a scheme for classifying the practice of PA into four categories – administrative, developmental, strategic, and role definition. This work was done to expand our understanding of performance appraisal and to highlight its uses in connection with other human resource management and development functions. The study finds that previous researchers devoted the most attention to PA conducted for administrative purposes, followed by PA for developmental purposes; the strategic category of PA was studied somewhat, whereas PA for purposes of role definition was almost ignored. The author offers a full-scale inventory of the purposes and uses of PA for researchers, performance raters and ratees. The study proposes that raters need to focus on the broader dimensions of PA, not simply its administrative functions.